Multilocus sequencing-based evolutionary analysis of 52 strains of Burkholderia pseudomallei in Hainan, China. (8th October 2019) - Fang, Y.; Hu, Z.; Chen, H.; Gu, J.; Hu, H.; Qu, L.; Mao, X.
Abstract: Previously, we reported a phylogenetic study of 98 Burkholderia pseudomallei clinical isolates from Hainan, China. Here, we update the B. pseudomallei strain library with 52 strains from newly identified cases dating from 2014 to 2017, analysed by multilocus sequence typing. Twenty-two sequence types (STs) were identified from the 52 cases, illustrating high genetic diversity; five of them (ST1480, ST1481, ST1482, ST1483 and ST1484) were novel. ST46, ST50 and ST58 predominated (34.6%) as was the case in the previous study (35.7%). An e-BURST map of the ST profiles of the two collections of isolates showed their genetic foundation to be largely unchanged. Neighbour-joining tree analysis was suggestive of a close phylogenetic relationship between the novel STs from this series and those first reported from Hainan (ST1105, ST1099, ST55 and ST1095). Moreover, the two novel STs (1481 and 1483) showed close similarity to ST58 which originated in Thailand indicating a close relationship between B. pseudomallei strains from both countries. The previously described allele profiles gmhD -36 and lepA -68 were found for the first time in our strain collections. Our study emphasises the importance of monitoring the epidemiological status and evolutionary trends of B. pseudomallei in China.